DNA-Induced Transformation in Drosophila: Evidence for Transmission without Integration - Fox, Allen S. (1970)
A key feature of the exosome model of transformation in Drosophila melanogaster is that the DNA segments responsible for the phenomenon are not integrated into the linear structure of the chromosomes. This feature is confirmed by the failure to find whole-body transformants in a series of large-scale experiments, and by the absence of evidence for integration under conditions favoring genetic exchange between chromosomes and introduced DNA.